Estimation of detection thresholds for audiovisual rotation gains - Nilsson, Niels Christian; Suma, Evan; Nordahl, Rolf; Bolas, Mark; Serafin, Stefania (Proceedings of the Workshop on Future Trends of Distributed Computing Systems, 2016)
Redirection techniques allow users to explore large virtual environments on foot while remaining within a limited physical space. However, research has primarily focused on redirection through manipulation of the visuals used to represent the virtual environment. We describe a within-subjects study (n=31) exploring if participants' ability to detect differences between real and virtual rotations is influenced by the addition of sound that is spatially aligned with its virtual source. The results revealed similar detection thresholds for conditions involving moving audio, static audio, and no audio. This may be viewed as an indication of visual dominance during scenarios such as the one used for the current study.